HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA PADA SISWA PUTRA EKSTRAKURIKULER SDN 9 MONTONG BAAN TAHUN PELAJARAN 2014/2015 - Mahsun, Mahsun (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The game of football is one of the most popular sport in the world. Those who helped popularize the game of football is not impossible because thanks to the rigorous training and seriousness in various aspects. One is training agility (Agility), which will help them move around freely, quickly and dodges from the attack , so we can do all that well and successfully, a football player has the good agility . The aim of the research is to know whether correlation between Agility with ball dribbling Skills in the Game of Football at Male Students Extracurricular SDN 9 Baan Montong Academic Year 2014 / 2015. Population in this study were all male students who follow extracurricular football in SDN 9 Montong Baan Academic Year 2014/2015 which amounted to 14 students, while the researchers use the entire population into sampling technique used in this study is population sampling . suitable with the purpose of this study, the method used is the test method works to obtain data agility using tests run back and forth (Shutlle run) and dribbling skills were measured using tests to dribble routes already obtained the results of data analysis value "rxy amounted to 0.586, while the magnitude of the numbers r table with a significant level of 5% and N = 14 is 0.532. This means that r count is greater than r table (0.586> 0.532) so it concluded that "there is a correlation between Agility with Ball Dribbling Skills in Student Games Men's Football at SDN 9 Montong Baan Extracurricular Academic Year 2014/2015